A novel inulin-type fructan from Asparagus cochinchinensis and its beneficial impact on human intestinal microbiota. (1st November 2020) - Sun, Qili; Zhu, Lixia; Li, Yixuan; Cui, Yongsheng; Jiang, Siliang; Tao, Ning; Chen, Hubiao; Zhao, Zhongzhen; Xu, Jun; Dong, Caixia
Highlights: An inulin-type fructan named ACNP was first isolated from Asparagus cochinchinensis . ACNP has a linear backbone composed of 2, 1- β -D-Fru f residues, ending with a (1→2) bonded α -D-Glc p . ACNP beneficially regulates human gut microbiota and promotes the production of SCFAs. ACNP has the potential to be used as a dietary supplement or drug to improve health. Abstract: A purified inulin-type fructan named ACNP ( Asparagus cochinchinensis neutral polysaccharide) with apparent molecular weight of 2690 Da was obtained from Asparagus cochinchinensis (Lour.) Merr. by ion-exchange and gel-filtration column chromatography. Structural analyses reveal that ACNP has a linear backbone composed of 2, 1- β -D-Fru f residues, ending with a (1→2) bonded α -D-Glc p . The impacts of ACNP on gut microbiota were then investigated by in vitro fermentation with human fecal cultures. The results showed that ACNP was digested by gut microbiota, while the pH value in the fecal culture of ACNP was greatly decreased, and total short-chain fatty acids, acetic, propionic, i-valeric and n-valeric acids were significantly increased. Moreover, ACNP regulated the fecal microbiota composition by stimulating the growth of Prevotella, Megamonas, and Bifidobacterium while depleting Haemophilus . Collectively, these results indicated that ACNP beneficially regulates gut microbiota, which thus suggested that ACNP has the potential to be used as a dietary supplement or drug to improve health.